(untitled) (Al-Qamar, 2022)
This paper studies the Shariʻah status of contemporary education. It argues that the holy prophet peace be upon him preached that Acquisition of knowledge is obligatory upon both Muslims male and female He also acknowledged the importance of travelling to far off place to enhance the experience Acquire knowledge even if you have to travel to China. Islamic philosophy of education envisages “righteous thinking and action” to make the individual aware about his purpose of creation and to identify himself and to have cognizance of Allah. Islamic concept of philosophy preaches that the purpose of life is “achievement of pleasure of Allah.” This pleasure does not restrict the human activities to mere worships of Allah but it educates the people to realize the system of rights of all the living creatures and also the non-living things which are the requirements to establish an exemplary worth living society.